Relação entre a qualidade do toque materno e o processamento neural do toque afetivo em bebês aos 6 meses de idade - Camillo, Juliana Bencini Nicoletti (2021)
The affective or social touch is one that occurs naturally in the context of social interactions between individuals, as in a mother-infant interaction. Fibers known as C-tactile are responsible for detecting this type of touch, which recruits somatosensory and social areas of the brain for processing. Furthermore, evidence suggests that contextual factors, such as the individual's history of tactile experiences, can modulate the perception and processing of affective touch. Very little is known about the importance of the relationship between these contextual factors and the involvement of CT fibers in the modulation of the neural response to affective touch in infants, especially during their first year of life. The present study aimed to investigate the association between the tactile behaviors used by the mother in moments of interaction with her infant and the infant's neural response to affective touch, at 6 months of age. Twelve mother infant dyads participated in this study, which were evaluated during a 9-minute interaction to codify the following tactile behaviors on the part of the mother: affectionate, stimulating / playful, instrumental, accidental / accessory, intrusive / negative and static touch. The mother-infant interaction was divided into 3 moments, with specific objectives: 1st episode - free play, 2nd episode - interaction without toys and 3rd episode - challenging interaction. The infant's brain response to affective touch was evaluated using the Functional Near Infrared Spectroscopy (fNIRS) technique, during a task in which the infant received an affective touch stimulus, made with the human hand, in the region of the right shoulder blade. Valid data on brain response to affective touch were obtained in 8 infants. The results showed brain activation in the somatosensory and temporal areas in response to the affective touch (apparently performed by the mother). In the interaction with their infants, mothers generally used accidental/accessory touch more frequently (especially in episodes involving toys), dedicating more time to static touch, while affectionate touch was the type of touch that mothers used less and devoted less time. Finally, in relation to the association analyses, we found that a more robust response in the infants' primary somatosensory cortex to affective touch was correlated with greater frequency and duration of maternal affectionate touch, as well as with longer duration of accidental/accessory touch throughout the mother-infant interaction. On the other hand, more attenuated responses in the pSTS region and in the infants' secondary somatosensory region to affective touch correlated with greater use and duration, respectively, of maternal intrusive / negative touch throughout the interaction. Although preliminarily, our results suggest that the quality of tactile stimulation (type, frequency and duration) received by infants at six months of age, during interaction with their mothers, may be related to their neural processing of affective touch.